Wash hand education and hand sanitizer preparation workshop to the community in order to prevent COVID-19 transmission - Laila, Lia; Marianne; Hanum, Tengku Ismanelly; Maha, Hetty Lendora (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Communicable disease, COVID-19 easily spreads through the respiratory droplets. Therefore, WHO recommends the physical distancing policy to prevent the transmission. However, the transmission of SARS-CoV2 virus causing COVID-19 occurred not only by human interaction, but also the things that had been touched by the people suffered COVID-19 have potential as the media for the virus transmission. Then, it is necessary to anticipate the worries in the form of correct wash hand application or using hand sanitizer. The activities that had been done were giving an education about the communicable disease, COVID-19, how it is spread and how to prevent it; performing correct hand wash and preparation of alcohol based hand sanitizer in the form of gel to the society of Belawan I neighborhoods, Medan Belawan District, Medan City. The survey analysis results showed that the community service that had been conducted in Belawan I neighborhoods gave benefits and elevated approximately 49.5% the knowledge of the community regarding the COVID-19 and hand sanitizer preparation.